Sekstorsi Sebagai Tindak Pidana Kekerasan Seksual Berbasis Elektronik dalam Sistem Hukum di Indonesia - Dea Tri Afrida; Ismansyah; Edita Elda (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2023)
Sextortion as part of Cyber Gender-Based Violence (KBGS) is a cybercrime that often occurs today. Sextortion is carried out by extorting or exploiting the victim materially or sexually by utilizing the victim's pornographic content. Prior to the promulgation of Law Number 12 of 2022 concerning Crimes of Sexual Violence (TPKS Law) on May 9 2022, the crime of sextortion was regulated separately and spread across several laws and regulations, where these regulations still had juridical weaknesses which led to overcoming sextortion crimes in Indonesia are not sufficient. This study discusses the form of sextortion arrangements in Indonesian criminal law. This research uses normative research methods with statutory and case approaches, with secondary data sources. The results of this study concluded that the forms of regulation of sextortion in Indonesian criminal law consist of criminal acts of decency, criminal acts of extortion, criminal acts of threats, criminal acts against the independence of others, criminal acts of pornography, and criminal acts of electronic-based sexual violence (KSBE). The existence of the TPKS Law has regulated formulations of sextortion crimes that are better and more comprehensive than formulations in the Criminal Code, the Pornography Law, and the ITE Law. The implementation of the TPKS Law is expected to be able to realize the prevention of sextortion crimes that reflect the values of justice and legal certainty.